Tumor-Background Ratio is an effective method to identify tumors and false-positive nodules in indocyanine-green navigation surgery for pediatric liver cancer - Feng, Jun; Qin, Hong; Yang, Wei; Cheng, Haiyan; Xu, Jiatong; Han, Jianyu; Mou, Jianing; Wang, Huanmin; Ni, Xin (Frontiers in Pediatrics, 2022)
Background: Indocyanine green (ICG) navigation surgery has been used for hepatoblastoma (HB) in children but the technique has been reported for using in other childhood liver cancers were rare. This article summarizes the application experience of ICG in HB and other childhood liver cancers in children and explores the role of fluorescence intensity measurement in identifying tumors. Methods: To summarize the clinical experience of children with liver cancer treated by ICG navigation surgery. The tumor and its surrounding tissue were photographed by near infrared during the operation. The fluorescence intensity of tumors, ICG (+) lesions and the normal liver was measured, and the Tumor-Background Ratio (TBR) was calculated. Results: A total of 11 children with liver cancer were injected intravenously with ICG one day before operation. With the help of ICG fluorescence navigation, there was no residual tumor at the surgical margin for all the children. Total fluorescence was seen in 2 cases, rim fluorescence in 2 cases, and partial fluorescence in 7 cases. 19 ICG false-positive nodules were found on the resection stump or residual liver tissue in 5 cases, and the TBR value of tumors was higher than that of false- positive nodules. 10 children have survived without disease. Conclusions: ICG navigation surgery is safe and feasible for liver cancer in children, which can enhance the visualization of the tumor during operation and provide more information about the location and boundaries of the tumor. This technique also has limitations, which can be affected by chemotherapy, tumor location, ICG administration regimen, and equipment. TBR is a effective method to identify tumor and noncancerous lesions.